ChemInform Abstract: Halogen‐Adjusted Chemoselective Synthesis of Fluorene Derivatives with Position‐Controlled Substituents. Issue 23 (May 2016) - Song, Juan; Sun, Wei; Li, Yali; Wei, Fuliang; Liu, Chao; Qian, Yan; Chen, Shufen
Abstract: The regioselectivity of the process depends on the ortho‐halogen substituent of the benzyl bromide.